Being in between the Gender in Indian Society: A Study on the Films Chitrangada and Nagarkirtan - Tonny, Afsarabinta Alam (Integrated Journal for Research in Arts and Humanities, 2024)
The Indian society is a patriarchal one believing in heterosexual normalcy, invalidating all other gender identities. Although people who are “in between” the gender have always desired for social acceptability, their existence is still not acknowledged in this society. Rudra, a gay and Puti, a transgender are the two protagonists from the films Chitrangada: The Crowning Wish (2012) and Nagarkirtan (2017) face challenges for not belonging to the existing gender binary in Indian society. Their journey is filled with toxicity and marginalization for their unconventional gender identity. This study focuses on how this patriarchal gender system has been oppressive towards the non-conformists. It also explores why homosexual and transgender individuals feel to undergo the transsexual transition to conform to the heterosexual dichotomy of the society. This is a qualitative content analysis. Considering two Indian films as its primary source, it explores several past researches as its secondary source. This article draws ideas from LGBTQ++ theory, "Gender Performativity" theory by Judith Butler, and "Representation" theory by Stuart Hall.